Cobalt–molybdenum synergistic catalysis for the hydrogenolysis of terephthalate-based polyesters. Issue 21 (19th October 2021) - Wu, Pengyu; Lu, Guoping; Cai, Chun
Abstract : Recyclable bimetallic catalyst CoMo@NC was prepared and efficiently catalyzed the hydrogenolysis of polymer plastics through the Co–Mo synergistic catalysis strategy. Abstract : Recycling of polyester waste has become a focus of global attention in recent years. Herein, a novel bimetallic catalyst, CoMo@NC derived from Mo@ZIF-CoZn, has been prepared, which can be applied in hydrogenolysis for recycling terephthalate-based polyesters (polyethylene terephthalate (PET) and polybutylene terephthalate (PBT)), converting PET to the valuable monomer terephthalic acid (PTA) in high yield within 10 hours at 260 °C, under atmospheric H2 . A distinct enhancement in the catalytic performance of this catalyst is observed when compared with monometallic catalysts, which can be ascribed to the "synergistic catalysis" between Mo-sites and Co-sites inside the bimetallic catalyst. The recyclability test indicated that this catalyst could be reused for at least six times with stable activity. This work highlights new possibilities for bimetallic catalysts applied in sustainable chemistry.